Asymmetric rivalry between strategic groups: response, speed of response and ex ante vs. ex post competitive interaction in the spanish bank deposit market - Ruiz, Francisco Mas; Nicolau, Juan Luis; Ruiz‐Moreno, Felipe (Strategic Management Journal, 2005)
Abstract The objective of this study is to examine asymmetric rivalry between strategic groups in a given industry. Two research hypotheses argue for the existence of asymmetric rivalry in the sense that strategic groups of small companies have a greater degree of response but a slower speed of response to the actions of strategic groups of large companies, than vice versa. To test this, we use an ex post approach that examines the news releases published on the strategic actions and reactions of firms. A third hypothesis compares ex ante competitive expectations with ex post asymmetric rivalry between strategic groups. To test this, we compare ex post news on actions/reactions with an ex ante approach that estimates conjectural variations. The empirical application carried out on bank deposits in the Spanish market defines strategic groups in terms of size due to the historical and institutional conditions of the industry (deregulatory change). The results obtained show that rivalry patterns between strategic groups in terms of company size can be predicted as asymmetric in the sense that smaller bank strategic groups have a greater degree of response (Stackelberg ‘leader–follower’ competitive interaction), and a slower speed of response to the actions of larger bank strategic groups than is found the other way around. Moreover, ex ante expectations of aggressiveness on the part of larger strategic groups characterize greater ex post reactions from the smaller‐size strategic groups. Therefore, the size distribution of strategic groups is valuable to research on complex industries with deregulation changes. Copyright © 2005 John Wiley & Sons, Ltd.